The Tumultuous Game of Legitimacy: Capital Contestation between Riggan, Mike, and Tabitha in Birdman (2014) - Alexei Wahyudiputra; Edi Dwi Riyanto (Anaphora : Journal of Language, Literary, and Cultural Studies, 2022)
The contemporary Hollywood cinematic landscape is commonly filled with popular films that seek mass legitimacy. It is different from theatrical works or Broadway that are specifically aimed at connoisseurs. The ample evidence of popular films infers that American cultural field constructs its logicality in effect of this system. It affects at how one distinctively perceives theatre or Broadway as “art” and films as “entertainment", leading the actors within them to seek to be legitimized as an “actor/artist” in a distinctive way. This article specifically aims to diagnose this condition through Alejandro Gonzalez Iñárritu’s film entitled Birdman (2014) that tells a story of a washed-up American film actor who wishes to revive his career on Broadway. The research utilizes Pierre Bourdieu’s theory on the mechanism of symbolic power, capital, and trajectories to reveal the dynamics of the field in legitimizing one’s status as an actor and the paths one takes to be legitimized as an artist. The findings suggest the asymmetrical position between Broadway and films leads to exertions of symbolic violence as portrayed by Birdman. The skillset to act is not a measurement for one to be called as an “actor”, rather it is the complex nexus between the field and the agent’s background that determines the legitimacy.